2022
DOI: 10.14639/0392-100x-n2055
|View full text |Cite
|
Sign up to set email alerts
|

Oral tongue carcinoma: prognostic changes according to the updated 2020 version of the AJCC/UICC TNM staging system

Abstract: SUMMARY Background This study aimed to evaluate the performance of the 2017 8 th TNM edition and the latest update in 2020 compared to the 7 th in a large cohort of patients affected by oral tongue squamous cell carcinoma (OTSCC), considering all stages. Materials and methods The cohort involved 300 patients affected by OTSCC treated with surgery. All cases were classified according to the 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…Considering the significance of IPLN metastasis, a suggestion of the inclusion of IPLN status in LN stage classification was proposed 18 , but this was not realized in the 8th AJCC N classification which was drafted based on head and neck squamous cell carcinoma 19 , prior literature described the official N stage could not well stratify the survival in salivary gland carcinoma 20 , our study also confirmed that the 8th AJCC N stage was not related to DM occurrence. It might be contributed by the distinct difference of biologic behaviour between the two kinds of disease, and the common death cause in parotid cancer was DM but not locoregional recurrence.…”
Section: Discussionsupporting
confidence: 61%
“…Considering the significance of IPLN metastasis, a suggestion of the inclusion of IPLN status in LN stage classification was proposed 18 , but this was not realized in the 8th AJCC N classification which was drafted based on head and neck squamous cell carcinoma 19 , prior literature described the official N stage could not well stratify the survival in salivary gland carcinoma 20 , our study also confirmed that the 8th AJCC N stage was not related to DM occurrence. It might be contributed by the distinct difference of biologic behaviour between the two kinds of disease, and the common death cause in parotid cancer was DM but not locoregional recurrence.…”
Section: Discussionsupporting
confidence: 61%
“…17 The 8 th TNM edition of the American Joint Committee on Cancer/International Union Against Cancer (AJCC/UICC) staging system introduced the tumor depth of invasion (DOI) at the T stage and the incorporation of extracapsular spread (ECS) at the N stage to improve its prognostic value. 18,19 Because the present study was retrospective, data referring to pretreatment imaging examinations and access to histological slides were no longer possible, and we were unable to reclassify the samples using the 8 th TNM edition. Despite this limitation, we believe that the follow-up period of the patients was longer than that in previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…However, the wide difference in oncological outcomes between the early and advanced stages did not change ( 48 50 ). Even if the 8 th TNM edition better stratifies the prognosis ( 43 , 51 ), the role of S/G is not considered.…”
Section: Discussionmentioning
confidence: 99%